Genotype of Cryptosporidiumspp. isolated from human of Al-Qadisiyah province Iraq. - Al-Jawasim-A .D.G; -Khaled M.J.A. (Al-Qadisiyah Journal of Pure Science, 2019)
Abstract:The current   study included examination of 100 stool sample from human was collected from AL-Qadisiyah province, from September 2018 until February 2019.the Microscopic examination  result showed  that oval or spherical shaped with dark pink color or red oocyst on blue ground and 22(22%) positive sample  out 100 case .  It was recorded that the highest rate 30% (3/10)  was seen  in September , but  the lowest  infection rate  13.3% (2/15) was seen in the month of December  with no significant differences at level (p<0.05.)  regarding  to age the high rate  of infection 26.31%(10/38)was found  in the  group less than a year , but  the lowest  infection  rate was observed in the  group( >12 years). There is no significant differences at p<0.05.between man  and women . In this study the N- PCR in molecular examination were  used ,the positive sample was13 (59.09%) out of 22 stool  sample.  Sequencing of a fragment of the  (18s  rRNA) gene (834 bp) that separated  from  many  different area  in AL-Qadisiyah government  recorded (75%)9/12 samplerelated to NCBI – Blast Cryptosporidium hominis isolates ,( 25%) 3/12 sampledisplay   closed  related to NCBI –Blast  Cryptosporidium  parvum .In Conclusion The current study concluded that phylogenetic tree and the homology sequences identity gives a clear differentiation of the types of Cryptosporidium parasites which can be isolated at high rates of human in AL- Diwaniyah province, which is likely to lead to an outbreak of Cryptosporidiosis in this province.